When the Real World Rejects, Social Media Welcomes: A Portrait of LGBT Identity in Postmodern Society - Wulanda, Agiva Early; Azzahra, Fatma; Putri, Risti Regina; Anggrayani, Sista; Hufad, Achmad; Achdiani, Yani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the role of social media in the formation of gender identity and sexual orientation, especially in the LGBT community in Indonesia, within the framework of postmodernism theory. This study examines how social media as a digital space allows individuals to express various versions of identity that are fluid, multiple, and contextual, while also presenting challenges in the form of social pressure, stigmatization, and psychosocial insecurity such as cyberbullying. Through a qualitative approach, this study describes the fragmentation of identity on social media that reflects the relativism of values in contemporary society. The results of the study indicate that although social media provides a space for support and validation for marginalized groups such as LGBT, there is an urgent need for social education and progressive policies to create an inclusive and safe digital environment. This study emphasizes the importance of balance between digital existence and real life in the process of positive and constructive identity formation.